Respostas

2013-11-30T20:46:59-02:00
A) a= 2
   b= -6
   c= -3

Δ = b² -4ac
Δ = -6² - 4 . 2 . (-3)
Δ = 36 -4 . 2 . (-3)
Δ = 60

x = -b +- √Δ / 2a
x = 6 +- √60 / 2.2
x = 6 +- 7,74 / 4
x1 = 6 + 7,74 / 4
x1 = 13,74 / 4
x1 = 3,43

x2= 6 - 7,74 / 4
x2 = -1,74 / 4
x2 = -0,43

b) Y= x²/2 = -x² -x/2 + 1/4
Y = 0,5x² = -x² -0,5x + 0,25
Y = 0,5x² + x² +0,5x = 0,25
Y= 1,5x² + 0,5x - 0,25 = 0

a = 1,5
b = 0,5
c = -0,25

Δ = 0,5² - 4 . 1,5 . (-0,25)
Δ = 25 - 4 . 1,5 . (-0,25)
Δ = 26,5

x = -0,5 +- √26,5 / 2 . 1,5
x = -0,5 +- 5,15 / 3

x1 = -0,5 + 5,15 / 3
x1 = 4,65 / 3
x1 = 1,55

x2 = -0,5 - 5,15 / 3
x2 = -5,65 / 3
x2 = -1,88
2 5 2